Ilościowe parametry oceny wypłacalności zakładów ubezpieczeń w Solvency II - Kurek, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the article the author discusses the issues of the quantitative parameters of solvency valuation in insurance companies within the confines of the project Solvency II. So far, solvency control levels have been attributed to those parameters without specifying supervisory entitlements connected with established thresholds. The issue of comparing guidelines of quantitative parameters in existing regulations - Solvency I with the quantitative thresholds in Solvency two has been also discussed. The analysis being carried out proves that simple comparison is not possible, as Solvency II includes number of additional elements being understood as evaluation of ''working quality" as well as evaluation of insurance company by the environment. However it shall be stressed that in relation to quantitative parameters those issues are brought up in more detailed way than in Solvency I. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 322-330